PENGUKURAN KINERJA PERBANKAN SYARIAH DENGAN PENDEKATAN BALANCE SCORECARD - Nurul Huda; Ivo Sabrina; Efendy Zain (ETIKONOMI, 2013)
The aim of this research is to measure the performance of Islamic banking using balance scorecard. Performance of Islamic Banking is seen with the Balanced Scorecard is used there are four perspectives, namely: finance, banking / internal business perspective, learning and growth, however in this study used only three perspektif , minus the customer's perspective. The third perspective is transformed into the five components of performance measurement variable Banking. The result of this research is learning and growth perspective for shariah compliance, legal, and institution has a very good score. For fundraising, financing performance and services for Islamic banking shariah compliance perspective has a good score. From financial report and social legitimacy has a good scoreDOI: 10.15408/etk.v12i1.1900